Belgium : 2008 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The global financial crisis has forced government intervention in major financial institutions in Belgium. This 2008 Article IV Consultation discusses that the boom in energy and food prices in early 2008 caused inflation to spike to well above the euro area average. Executive Directors have commended the authorities for their prompt and decisive intervention as the Belgian banking sector began to face severe pressure in September 2008. Directors have also encouraged the authorities to allow fiscal stabilizers to operate fully, and welcomed the moderate discretionary stimulus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet